An Integrated Sustainable Horticultural Farming in Peatland Area for Food Security and Circular Economy Sidrap Community - Uzlifatul Jannah Lizana; Muhammad Khilmi; Choirul Dwi Cahyo (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
PT Pertamina Gas Operation Kalimantan Area (OKA) initiate Community Empowerment Program in peatland society, titled TAMAN Sidrap. The program develops an integrated sustainable farming method, which aims to increase horticultural crops productivity in peatland area and decrease the cost of agricultural production for food security. In program implementation, TAMAN Sidrap involve 4(four) farmers community in Sidrap Village with different activities in each group that are integrated to increase circular economy. This Community Empowerment Program has been running for 3 (three) years, and has made a positive economic, social and environmental impacts on the farming communities in Sidrap Village including 42% increase productivity of agricultural in peatland area, 33% efficiency horticultural cost production, 7 days accelerated harvest period, and 68% decrease a fertilizer cost by producing compost from utilization of agricultural waste. Besides, the community has been improving agricultural products and manage the agricultural market by itself.